On space-time coding for free-space optical systems - Bayaki, Ehsan; Schober, Robert (IEEE Transactions on Communications, 2010)
Atmospheric turbulence-induced fading is one of the main impairments affecting free-space optics (FSO) communications. In this paper, we consider FSO systems with intensity modulation and direct detection (IM/DD) and derive a closed- form expression for the asymptotic pairwise error probability of general FSO space-time codes (STCs) for two lasers and an arbitrary number of photodetectors for channels suffering from Gamma-Gamma fading. Furthermore, we provide a simple design criterion for FSO STCs which is used to establish the quasi-optimality of previously proposed FSO repetition codes. We also show that STCs optimized for RF systems achieve full diversity in FSO systems but are suboptimal as far as the coding gain is concerned. Simulation results confirm the analytical findings of this paper. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Intensity modulation and direct detection; gamma-gamma fading; Repetition coding; Space-time coding; free-space optical systems